2016
DOI: 10.1073/pnas.1521069113
|View full text |Cite
|
Sign up to set email alerts
|

Cd47-Sirpα interaction and IL-10 constrain inflammation-induced macrophage phagocytosis of healthy self-cells

Abstract: Rapid clearance of adoptively transferred Cd47-null (Cd47−/−) cells in congeneic WT mice suggests a critical self-recognition mechanism, in which CD47 is the ubiquitous marker of self, and its interaction with macrophage signal regulatory protein α (SIRPα) triggers inhibitory signaling through SIRPα cytoplasmic immunoreceptor tyrosine-based inhibition motifs and tyrosine phosphatase SHP-1/2. However, instead of displaying self-destruction phenotypes, Cd47−/− mice manifest no, or only mild, macrophage phagocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(139 citation statements)
references
References 66 publications
12
121
0
Order By: Relevance
“…Yet, depending u n o p s a n t i -R h D p a t i e n t I p a t i e n t I I p a t i e n t I I I p a t i e n t I V p a t i e n t V p a t i e n t V I a n t i -G P A Figure 7D). Although Bian et al showed this same effect in vivo in mice for multiple stimuli, 34 in our assay other stimuli did not have this effect. Overall, our data demonstrate that various inflammatory mediators can lower the threshold for phagocytosis of IgG-opsonized RBCs by neutrophils.…”
Section: Neutrophil Priming Enhances Erythrophagocytosissupporting
confidence: 53%
“…Yet, depending u n o p s a n t i -R h D p a t i e n t I p a t i e n t I I p a t i e n t I I I p a t i e n t I V p a t i e n t V p a t i e n t V I a n t i -G P A Figure 7D). Although Bian et al showed this same effect in vivo in mice for multiple stimuli, 34 in our assay other stimuli did not have this effect. Overall, our data demonstrate that various inflammatory mediators can lower the threshold for phagocytosis of IgG-opsonized RBCs by neutrophils.…”
Section: Neutrophil Priming Enhances Erythrophagocytosissupporting
confidence: 53%
“…In nonhuman primates, therapeutic dosing of CD47-blocking agents can be achieved while limiting side effects (11, 30). IL10 appears to prevent macrophages from attacking healthy cells when the CD47/SIRPα interaction is disrupted (55); other factors that regulate the response to treatment likely depend on a balance between pro-phagocytic and other inhibitory signals, and the identification of these signals remains an active area of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, CD47 −/− cells are cleared rapidly when they are adoptively transferred to the congeneic wild-type mice [15]. However, it was recently shown that CD47-SIRPα axis, while crucial, represents just one mechanism that controls phagocytic behavior [16]. Indeed, CD47 −/− mice do not manifest significant self-destruction phenotype unless they are in inflammatory conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, CD47 −/− mice do not manifest significant self-destruction phenotype unless they are in inflammatory conditions. Inflammatory cytokines stimulate protein kinase C-spleen tyrosine kinase (PKC-Syk) signaling pathway (which IL-10 negatively regulates), which then activates macrophage to target self cells [16]. Combined, these findings suggest a potential mechanism for anemia of chronic disease and that rhesus (Rh)-null individuals, who have <25% of normal CD47 levels, may be particularly vulnerable to anemia under inflammatory conditions and infections [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation